Model of Utilizing Discovery Learning to Improve Mathematical Learning Achievements - Ponidi, Ponidi; Waziana, Winia; Kristina, Marilin; Gumanti, Miswan (CV. Creative Tugu Pena, 2020)
The background of this classroom action research was to find out the low level of learning achievement of fourth grade students of SDN 2 Suban on Mathematics. This is because the learning model used is less attractive to students. The researcher conducted this study with the aim of analyzing the design of learning, the process of learning activities, learning models, and learning achievement of fourth grade students on Thematic subjects. Based on the fact that the student's learning outcomes are low, the writer conducts classroom action research with the intention of improving student learning outcomes. Collaborating with fellow writers trying to use the Discovery Learning model in learning carried out in the first cycle and second cycle, to improve the learning achievement of fourth grade students of SDN 2 Suban. The plan for improving learning through this research turns out that using the Discovery Learning model can improve student learning achievement. From the evaluation results, it can be seen that the percentage of learning outcomes of students who can achieve KKM with the acquisition of the percentage of pre-cycle 30%, cycle I 65%, cycle II 91%. Thus the author feels the need to master and use various learning models in each learning activity in the School. Keywords: Discovery Learning, Mathematics and Learning Achievement